New Israeli sonographic estimated fetal weight growth curves as compared to current birth weight growth curves: On what should diagnosis of intrauterine growth disorders be based? - Sapir, A; Khayyat, I; Rabinowitz, R; Samueloff, A; Drukker, L; Sela, H (Israeli Medical Association, 2017)
Background Two types of growth curves are commonly used to diagnose fetal growth disorders: neonatal birth weight (BW) and sonographic estimated fetal weight (EFW). The debate as to which growth curve to use is universal. Objectives To establish sonographic EFW growth curves for the Israeli population and to assess whether the use of the BW growth curves currently adapted in Israel leads to underdiagnosis of intrauterine growth disorders. Methods Biometric data collected during a 6 year period was analyzed to establish sonographic EFW growth curves between 15–42 weeks of gestation for the Israeli population. Growth curves were compared to previously published sonographic EFW growth curves. A comparison with the Israeli BW growth curves was performed to assess the possibility of underdiagnosis of intrauterine growth disorders. Results Out of 42,778 sonographic EFW studies, 31,559 met the inclusion criteria. The sonographic EFW growth curves from the current study resembled the EFW curves previously published. The comparison of the current sonographic EFW and BW growth curves revealed under-diagnosis of intrauterine growth disorders during the preterm period. Four percent of the fetuses assessed between 26–34 weeks would have been suspected of being growth restricted; 2.8 percent of the fetuses assessed between 30–36 weeks would have been suspected of having macrosomia, based on the BW growth curves. Conclusions New Israeli sonographic EFW growth curves resemble previously published sonographic EFW curves. Using BW growth curves may lead to the under-diagnosis of growth disorders. We recommend adopting sonographic EFW growth to diagnose intrauterine growth disorders.